2019
DOI: 10.1186/s12859-019-2619-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of linear models and missing value imputation for the analysis of peptide-centric proteomics

Abstract: BackgroundSeveral methods to handle data generated from bottom-up proteomics via liquid chromatography-mass spectrometry, particularly for peptide-centric quantification dealing with post-translational modification (PTM) analysis like reversible cysteine oxidation are evaluated. The paper proposes a pipeline based on the R programming language to analyze PTMs from peptide-centric label-free quantitative proteomics data.ResultsOur methodology includes variance stabilization, normalization, and missing data impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The data analysis pipeline consists of: (1) data normalization and variance-stabilization, (2) data filtering, (3) missing data imputation, (4) linear model analysis (limma), (5) differential analysis using limma output and fold change criteria, (6) multiple imputation and binomial testing, (7) time-series clustering analysis, (8) structure-reactivity clustering analysis of Cys residues, and (9) functional Gene Ontology (GO) annotation analysis. The first peptide analysis steps follow the implementation of the peptide-centric proteomics pipeline described in Berg et al (2019), which has demonstrated very good performance for analysis of reversible oxidized cysteines on a benchmark dataset. An important result from our previous study was the significant performance improvement obtained when using a linear model in combination with multiple data imputations for comparative analysis of large-scale reversible Cys oxidation datasets.…”
Section: Strategy For Quantitative Profiling Of Reversible Cys Oxidatmentioning
confidence: 99%
See 3 more Smart Citations
“…The data analysis pipeline consists of: (1) data normalization and variance-stabilization, (2) data filtering, (3) missing data imputation, (4) linear model analysis (limma), (5) differential analysis using limma output and fold change criteria, (6) multiple imputation and binomial testing, (7) time-series clustering analysis, (8) structure-reactivity clustering analysis of Cys residues, and (9) functional Gene Ontology (GO) annotation analysis. The first peptide analysis steps follow the implementation of the peptide-centric proteomics pipeline described in Berg et al (2019), which has demonstrated very good performance for analysis of reversible oxidized cysteines on a benchmark dataset. An important result from our previous study was the significant performance improvement obtained when using a linear model in combination with multiple data imputations for comparative analysis of large-scale reversible Cys oxidation datasets.…”
Section: Strategy For Quantitative Profiling Of Reversible Cys Oxidatmentioning
confidence: 99%
“…Detailed evaluation of the steps used in the enrichment of reversible Cys oxidation was performed as described in Berg et al (2019). Briefly, each replicate and 50 mg of TPS6B (GE Healthcare Bio-Sciences) resin slurry were combined and incubated in a Thermomixer for 2 h at 30°C and 850 rpm to allow protein binding via Cys thiols.…”
Section: Protein-level Cys Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Best Paper Award, MCBIOS 2018 : Phillip Berg et al, “Evaluation of Linear Models and Missing Value Imputation for the Analysis of Peptide-Centric Proteomics” [1].…”
Section: Introductionmentioning
confidence: 99%